Performance modeling of the weather impact on a utility-scale PV power plant in a tropical region - Gopi, Ajith; Sudhakar, K.; Ngui, Wai Keng; Krishnan, Ananthu R.; Priya, S. Shanmuga (Hindawi, 2021)
Solar photovoltaics and the associated applications are now considered the most promising technologies for a sustainable future. The performance of the PV power plants is not studied in detail with respect to the influence of various weather parameters like rain, relative humidity, and atmospheric pressure on energy generation. The objective of this research work is to analyze and model the weather impact of a utility-scale PV power plant in a tropical region. The methodology involves the detailed analysis of the PV plant performance for various weather seasons and modeling the energy generation based on important weather parameters obtained from a Solar Radiation Resource Assessment (SRRA) station installed at the PV power plant location itself. Solar generation and its performance are affected during the rainy seasons, and it turns out to be a typical phenomenon in the humid tropical region. A regression model of solar generation for all the weather seasons is generated based on different weather parameters.